Critical challenges in access management schemes for smartphones: an appraisal - Mehraj, Tehseen; Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Anwar, Farhat; Jusoh, Ahmad Zamani (Springer, Singapore, 2019)
A growing trend exerted by current users in accessing sensitive data and performing critical data exchanges predominantly highlights the proliferation usage of mobile phone devices by users for accessibility. There exists a demand for a security solution capable of thwarting the existing threats while offering extended support, at the same time conserving user adaptability. In this research, an intensive survey has been conducted in which various security solutions based on biometric and non-biometric access management schemes have been contemplated. A lack of absolute or standard access control management scheme capable of delivering a secure and feasible solution on mobile phones persists. Each of the works offered by researchers has been single-handedly evaluated. Finally, loopholes and open challenges were deduced from the study conducted.